Exploring the use of positive psychology interventions in brain injury survivors with challenging behaviour. (June 2014) - Andrewes, H. E.; Walker, V.; O'Neill, B.
Abstract Objective: To investigate the feasibility and effectiveness of conducting two positive psychology interventions to improve mood and self-concept with survivors of traumatic brain injury (TBI), within a neuro-rehabilitation hospital. Method and procedures: Ten patients with brain injury were randomly allocated to an intervention and control group. The efficacy of the first intervention, 'three positive things in life' was measured via Seligman's Authentic Happiness Index (AHI), at base-line, directly following the intervention and at the end of the 12-week group programme. The second intervention, the 'Value in Action (VIA) signature strengths intervention' was measured by the Head Injury Semantic Differential Scale (HISDS) at baseline and at the end of the group. Results: Compared to baseline and control group scores, the AHI index showed an increase in the intervention group's happiness following the intervention and at the end of the 12-week programme, albeit the latter increase was non-significant. The HISDS showed non-significant improvement in self-concept and reduction in polarization of the self in the present, future and past in the second intervention. Anecdotal evidence revealed a clear improved mood following the interventions. Conclusion: This study shows promising results for the effectiveness of Positive Psychology interventions and methods to improve feasibility when applying this treatment within a hospital setting.